Visible Success and Invisible Failure in Post-Crisis Reform in the Republic of Korea : Interplay of the Global Standards, Agents, and Local Specificity - Lee, Keun (World Bank, Washington, DC, 2012)
The reform package in post-crisis Korea was one of the most comprehensively designed and decisively implemented. Though impressed by the quick recovery, many are now raising doubts about real changes in the economy, as the result of a cost-benefits analysis: While the business climate is more stable and supportive, the economy is suffering from weak investment and rising unemployment. This study views the Korean story as one of "visible success and invisible failure," based on the following findings: First, while some new laws were enacted and several quantifiable targets met, little real progress was made in changing institutional conventions, habits, and beliefs, such as enhancing transparency in management or trust in labor relations. Second, the reform process involved tension between global standards and local specificity, which accounts for the mixed results. Third, special interest politics at the implementation stage, plus the complexities caused by increasing democratization and globalization, have undermined the authorities' implementation capacity, which accounts for uneven outcomes of the reform. While globalization necessitates increasing flexibility, Korean managers are now facing much stronger labor unions. The outcome is not a fully flexible but segmented labor market, divided between the core, unionized workers and unorganized peripheral workers, and between the one overprotected and the other underprotected. Fourth, it is important to have an effective system of legislative bargaining to help resolve disputes. Only with this institutional vehicle will special interest groups reach some consensus. Korea tried to overhaul its financial system and achieve substantial financial liberalization in the early 1990s but those attempts were partly aborted and partly distorted, which paved the way for the financial crisis in 1997. This was due to the lack of clear consensus, without which reforms are more likely to be aborted or be unsuccessful. Fifth, implementation problems stem from institutional complementarities and inappropriate sequencing. One logical sequence might be banking reform, corporate governance, labor relations, and then finally business restructuring. Now, an emerging question is whether the reform blueprint was right. Post-crisis Korea just tried to be more market- or Anglo-Saxon model-oriented without paying attention to growth potential. While firms have now lowered their debt ratios, they are not borrowing to fund investments. The issue of right or wrong blueprint underscores the need to define the reform goal correctly. The goals of reform should not just be a move toward a market-oriented economy but toward a growth-oriented one or a pro-growth market-oriented one.